Researching creative writing - Jen Webb (Frontinus Ltd, 2015)
Creative writers who are also students or academics face two apparently contradictory imperatives: the need to answer important research questions, and the need to produce works of the imagination. The two activities depend on very different thinking processes, use language differently, and address different audiences. Yet they are not irreconcilably different: writers, whether academic or creative, tend to investigate the world around us, explore what we as human beings know and how we know it, test facts and common sense, and try to establish what really matters. And whether the result is a scholarly essay, a poem, a novel or a playscript, the writer faces similar challenges: how to convey the ideas, information, logical and emotional aspects that were a part of the work. Writer-researchers need to attend to the formulation of research questions, the selection of methodology and research methods, such practical aspects of writing and research as dealing with other people, and how the outputs are managed, analysed, interpreted and disseminated. When these issues are managed appropriately, research practices can invigorate writing, creative practices can invigorate research, and creative writing can operate as a mode of knowledge generation, a way of exploring problems and answering questions that matter. Jen Webb is Distinguished Professor, Creative Practice, at the University of Canberra.